Axitinib and sorafenib are potent in tyrosine kinase inhibitor resistant chronic myeloid leukemia cells. Issue 1 (December 2016) - Halbach, Sebastian; Hu, Zehan; Gretzmeier, Christine; Ellermann, Julia; Wöhrle, Franziska; Dengjel, Jörn; Brummer, Tilman
Abstract Background Chronic myeloid leukemia (CML) is driven by the fusion kinase Bcr-Abl. Bcr-Abl tyrosine kinase inhibitors (TKIs), such as imatinib mesylate (IM), revolutionized CML therapy. Nevertheless, about 20 % of CMLs display primary or acquired TKI resistance. TKI resistance can be either caused by mutations within the Bcr-Abl kinase domain or by aberrant signaling by its effectors, e.g. Lyn or Gab2. Bcr-Abl mutations are frequently observed in TKI resistance and can only in some cases be overcome by second line TKIs. In addition, we have previously shown that the formation of Gab2 complexes can be regulated by Bcr-Abl and that Gab2 signaling counteracts the efficacy of four distinct Bcr-Abl inhibitors. Therefore, TKI resistance still represents a challenge for disease management and alternative therapies are urgently needed. Findings Using different CML cell lines and models, we identified the clinically approved TKIs sorafenib (SF) and axitinib (AX) as drugs overcoming the resistance mediated by the Bcr AblT315I mutant as well as the one mediated by Gab2 and LynY508F . In addition, we demonstrated that AX mainly affects the Bcr-Abl/Grb2/Gab2 axis, whereas SF seems to act independently of the fusion kinase and most likely by blocking signaling pathways up- and downstream of Gab2. Conclusion We demonstrate that SF and AX show potency in various and mechanistically distinct scenarios of TKI resistance, including Bcr-AblT315I as well as Lyn- and Gab2-mediated resistances. Our data invites for further evaluation und consideration of these inhibitors in the treatment of TKI resistant CML.